PENGARUH KOMUNIKASI INTERPERSONAL TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PADA PEGAWAI DINAS PEKERJAAN UMUM DAN PENATAAN RUANG PROVINSI RIAU - Ilva Novira; Evawani Elysa Lubis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Humans as social beings need other people to interact with each other. This is a fact that most human persons are formed from the results of social interaction with each other. Communication can be carried out directly verbally without going through media intermediaries between two people or groups actively and interactively known as interpersonal communication. Human resources are the most important assets in an organization, because they are the source that controls the organization and maintains and develops the organization in the face of various demands of the times. Therefore there is a formal description of the behavior that must be done (intra-role), and that is not formally described by the employee (extra-role). This is commonly known as Organizational Citizenship Behavior (OCB). The purpose of this study was to determine how much influence interpersonal communication has on Organizational Citizenship Behavior (OCB) on employees of the Public Works Department and Spatial Planning of Riau Province.The method used in this study is an explanatory quantitative method, with data collection techniques through questionnaires. The location of the study was conducted at the Office of the Public Works and Spatial Planning Office of Riau Province, located on Jl. S.M. AMIN No. 92. The total sample of this study was 76 respondents. Sampling using accidental sampling technique. The researcher used simple linear regression analysis, to find out how much influence the two variables had. Management of questionnaire data is done using the Windows version 23 Product and Service Solution (SPSS) Statistics program.The results obtained from a simple linear regression analysis in this study is that there is an influence between interpersonal communication on Organizational Citizenship Behavior (OCB) on employees of the Public Works Department and Spatial Planning of Riau Province amounting to 32.6% which are categorized as weak while the rest are influenced by other factors. not in this study.Keyword : representation, feminsm, semiotic